Paediatric health-care professionals: Relationships between psychological distress, resilience and coping skills - McGarry, Sarah; Girdler, Sonya; McDonald, A.; Valentine, J.; Lee, S.; Blair, E.; Wood, Fiona; Elliott, Catherine (Blackwell Scientific Publications, 2013)
Aim: To investigate the impact of regular exposure to paediatric medical trauma on multidisciplinary teams in a paediatric hospital and the relationships between psychological distress, resilience and coping skills. Method: Symptoms of post-traumatic stress disorder, secondary traumatic stress, depression, anxiety, stress, burnout, compassion satisfaction, resilience and coping skills were measured in 54 health professionals and compared with published norms. Results: Participants experienced more symptoms of secondary traumatic stress (P < 0.01), showed less resilience (P = 0.05) and compassion satisfaction (≥0.01), more use of optimism and sharing as coping strategies, and less use of dealing with the problem and non-productive coping strategies than comparative groups. Non-productive coping was associated with more secondary traumatic stress (r = 0.50, P = 0.05), burnout (r = 0.45, P = 0.01), post-traumatic stress disorder (r = 0.41, P = 0.05), anxiety (r = 0.42, P = 0.05), depression (r = 0.54, P = 0.01), and stress (r = 0.52, P = 0.01) and resilience was positively associated with optimism (r = 0.48, P = 0.01). Health professionals <25 years old used more non-productive coping strategies (P = 0.05), less ‘sharing as a coping strategy’ (P = 0.05) and tended to have more symptoms of depression (P = 0.06). Conclusion: Paediatric medical trauma can adversely affect a health professional's well-being, particularly those <25 years of age who make less use of positive coping strategies and more use of non-productive coping. These findings will assist the development of effective and meaningful interventions for health professionals working in paediatric hospitals.